Development of a facile system for mass production of Brugia malayi in a small-space laboratory - Atiporn Saeung (2018)
Brugia malayi is one of the important lymphatic filarial nematodes that cause elephantiasis and disability in humans in the Asian region. Mass production at any stage of this nematode in both small laboratory animal hosts and mosquito vectors is still necessary in order to continue various research aspects. This study elucidated on the use of nonblood feeding or the autogenous Ochlerotatus togoi (Thailand strain) and male Mongolian jird (Meriones unguiculatus) system. This has brought about a low-cost and highly-effective procedure for the mass production of blood containing microfilariae, infective (L3) larvae, and adults of B. malayi under nonanimal-blood-feeding insectary and small-space animal-house conditions. The highly-infective rates (human-heparinized blood, 86.67-93.33; swine-heparinized blood, 83.33-96.67; bovine-heparinized blood, 76.67-80; chicken-heparinized blood, 73.33-76.67) and parasite loads (human-heparinized blood, 10.58-12.36; swine-heparinized blood, 8.40-10.38; bovine-heparinized blood, 9.75-9.91; chicken-heparinized blood, 3.41-4.65) of autogenous O. togoi to B. malayi and high numbers of adults recovered from ten B. malayi-infected male jirds (total = 327, 16-52) are good supportive evidence. In addition, all special techniques required for succeeding in the establishment of a facile system regarding these matters are detailed. © 2013 Springer-Verlag Berlin Heidelberg.